2006
DOI: 10.4319/lo.2006.51.2.1125
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of storm-induced suspension interflow in subtropical Feitsui Reservoir, Taiwan

Abstract: A storm‐induced suspension interflow (a kind of turbidity current) in subtropical deep (113‐m maximum depth) Feitsui Reservoir, Taiwan, was traced and simulated for both water quantity and quality control. To trace the path of the turbidity current, the spatial and temporal distributions of water temperature, turbidity, and concentration of total phosphorus were obtained weekly from seven sampling sites at 10‐m intervals vertically. These were obtained to trace the path of the turbidity current. A hydrodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The density difference between inflow and ambient water may arise from both temperature differences and variations in solute concentrations (Chen et al, 2006;Chung et al, 2009;An et al, 2012;An and Julien, 2014), and the inflow can be a tributary from an upstream river, transferred water from another reservoir or contaminant spill from a location (Gu and Chung, 2003;de Cesare et al, 2006;Umeda et al, 2006). An overflow (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The density difference between inflow and ambient water may arise from both temperature differences and variations in solute concentrations (Chen et al, 2006;Chung et al, 2009;An et al, 2012;An and Julien, 2014), and the inflow can be a tributary from an upstream river, transferred water from another reservoir or contaminant spill from a location (Gu and Chung, 2003;de Cesare et al, 2006;Umeda et al, 2006). An overflow (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A sequence of processes involving phosphate is expected to occur at the site. Bound phosphate would be released as dissolved phosphate in a reducing environment and transported upward to the euphotic zone (Robarts et al 1998;Chen et al 2006;Tseng et al 2010). In the present study, positive correlations were found between phytoplankton responses and runoff.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the rough topography, precipitation is highly variable, ranging from 3500 mm in the southwest portion of the FRW to more than 5000 mm in the northeast during 2001-2010. This area is covered mostly by natural secondary forests dominated by tree species within the Fagaceae and Lauraceae families (Chen, 1993). Because the FRW is a water resource protection area, agricultural activities are limited to pre-existing agriculture lands, mostly tea plantations (1200 ha).…”
Section: Study Regionmentioning
confidence: 99%